Visual memory for feature bindings: The disruptive effect of responding to new perceptual input. - Fiacconi, Chris M.; Milliken, Bruce (Quarterly Journal of Experimental Psychology, 2013)
In the current study, we examined how short-term memory for location-identity feature bindings is influenced by subsequent cognitive and perceptual processing demands. Previous work has shown that memory performance for feature bindings can be disrupted by the presentation of subsequent visual information, particularly when this information is similar to that held in memory. The present study demonstrates that memory performance for feature bindings can be profoundly disrupted by also requiring a response to visual information presented subsequent to the visual memory array. Across five experiments, memory for a location-identity binding was substantially impaired following a localization response to a following item that matched the location but mismatched the identity of the memory target. The results point to an important role for action in the episodic integration processes that control short-term visual memory performance.